Target position uncertainty during visually guided deep-inspiration breath-hold radiotherapy in locally advanced lung cancer. Issue 1 (April 2017) - Scherman Rydhög, Jonas; Riisgaard de Blanck, Steen; Josipovic, Mirjana; Irming Jølck, Rasmus; Larsen, Klaus Richter; Clementsen, Paul; Lars Andersen, Thomas; Poulsen, Per Rugaard; Fredberg Persson, Gitte; Munck af Rosenschold, Per
Abstract: Purpose: The purpose of this study was to estimate the uncertainty in voluntary deep-inspiration breath-hold (DIBH) radiotherapy for locally advanced non-small cell lung cancer (NSCLC) patients. Methods: Perpendicular fluoroscopic movies were acquired in free breathing (FB) and DIBH during a course of visually guided DIBH radiotherapy of nine patients with NSCLC. Patients had liquid markers injected in mediastinal lymph nodes and primary tumours. Excursion, systematic- and random errors, and inter-breath-hold position uncertainty were investigated using an image based tracking algorithm. Results: A mean reduction of 2–6 mm in marker excursion in DIBH versus FB was seen in the anterior-posterior (AP), left–right (LR) and cranio-caudal (CC) directions. Lymph node motion during DIBH originated from cardiac motion. The systematic- (standard deviation (SD) of all the mean marker positions) and random errors (root-mean-square of the intra-BH SD) during DIBH were 0.5 and 0.3 mm (AP), 0.5 and 0.3 mm (LR), 0.8 and 0.4 mm (CC), respectively. The mean inter-breath-hold shifts were −0.3 mm (AP), −0.2 mm (LR), and −0.2 mm (CC). Conclusion: Intra- and inter-breath-hold uncertainty of tumours and lymph nodes were small in visually guided breath-hold radiotherapy of NSCLC. Target motion could be substantially reduced, but not eliminated, using visually guided DIBH.